SOCIAL SCIENCE VERSUS SOCIAL CLASS CATEGORY - González Cárdenas, Victoria Eugenia (2014)
This article seeks to establish continuity between the beginning of the Marxist theory ofcapitalist society in European nineteenth century to the post-Marxism of contemporarycapitalist society, having as theme the category of social class in sociological thoughtwithin his long career in the social historical development of human and social sciences, ingeneral and sociology, in particular. It also presents the analysis of social class in the investigationof economic inequality raised by the analytical Marxism and the contributions ofEric Olin Wright, one of its leading representatives, with the idea of contradictory positionson class relations and the proposal the concept of class structure at the micro level ofanalysis for empirical research.